The Effect Of Training (Diklat) And Work Motivation On The Performance Of State Civil Apparatus In Singkawang City, West Borneo - Puteri Arini Pane; Andriyastuti Suratman (International Journal of Economics, Business and Innovation Research, 2025)
This study examines the effect of training and motivation on the performance of State Civil Apparatus (ASN) in Singkawang City. The main objectives of this study are to analyze the effect of training on work motivation, the effect of training on performance, and the effect of motivation on performance. This data was collected through a structured questionnaire distributed to 100 ASN respondents, ensuring a comprehensive understanding of the variables involved. This questionnaire was specifically designed to measure variables relevant to training, motivation, and performance. The collected data were analyzed using SPSS statistical software. Descriptive analysis was used to describe the characteristics of respondents and research variables. Inferential analysis, such as correlation and linear regression tests, were used to test the research hypotheses. The results showed that training and work motivation had a positive and significant effect on ASN performance in Singkawang City. This study provides practical implications for policy makers and organizational leaders to design effective training programs in improving ASN motivation and performance. This study also contributes theoretically to the development of human resource management science, especially in the context of ASN performance.